Demonstrate change. (2nd December 2020) - Caswell, Jo
Abstract : Jo Caswell explains what to expect from Ofsted's 'interim visits' which will focus strongly on your setting's safeguarding arrangements. Be ready to show how you are supporting and reassessing the needs of vulnerable children.